2013
DOI: 10.1038/jid.2013.52
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of Glutathione Peroxidase 4 in Mouse Skin Epithelial Cells Impairs Postnatal Hair Follicle Morphogenesis that Is Partially Rescued through Inhibition of COX-2

Abstract: Selenoproteins are essential molecules for the mammalian antioxidant network. We previously demonstrated that targeted loss of all selenoproteins in mouse epidermis disrupted skin and hair development and caused premature death. In the current study we targeted specific selenoproteins for epidermal deletion to determine whether similar phenotypes developed. Keratinocyte-specific knockout mice lacking either the glutathione peroxidase 4 (GPx4) or thioredoxin reductase 1 (TR1) gene were generated by cre-lox tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 49 publications
2
49
0
Order By: Relevance
“…Kumagai et al (2004) reported upregulation of PTGS2 by 4-HNE, an end product of oxidized lipids in an atherosclerosis model. Moreover, DNA microarray analysis of gene expression in skin tissue samples obtained from Gpx4 -deficient mice identified Ptgs2 as a key gene upregulated as a consequence of Gpx4 loss (Sengupta et al, 2013). Taken together, these data confirm that PTGS2 upregulation is a suitable marker for the lipid peroxidation that occurs during GPX4-regulated ferroptosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kumagai et al (2004) reported upregulation of PTGS2 by 4-HNE, an end product of oxidized lipids in an atherosclerosis model. Moreover, DNA microarray analysis of gene expression in skin tissue samples obtained from Gpx4 -deficient mice identified Ptgs2 as a key gene upregulated as a consequence of Gpx4 loss (Sengupta et al, 2013). Taken together, these data confirm that PTGS2 upregulation is a suitable marker for the lipid peroxidation that occurs during GPX4-regulated ferroptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Systemic deletion of Gpx4 in mice causes embryonic lethality, which was not observed when other Gpx genes were deleted (Ran et al, 2004), suggesting a unique role for Gpx4 in physiology. Four groups independently created conditional Gpx4 knockout mice and analyzed the cell death mechanisms after Gpx4 inhibition (Seiler et al, 2008; Sengupta et al, 2013; Ueta et al, 2012; Yoo et al, 2012). Lipid peroxidation was observed in all knockout models, highlighting the importance of Gpx4 for protecting cells from detrimental effects of lipid peroxides.…”
Section: Discussionmentioning
confidence: 99%
“…Bathing with hydrogen reduced water (HRW) before exposure to UV B significantly reduced the levels of skin damage induced by the UV B, accompanying significant increase in activity of GSH-Px [22]. Keratinocyte-specific knockout mice lacking the glutathione peroxidase 4 (GSHPx 4), an isoenzyme of GSH-Px, increased lipid peroxidation in cultured keratinocytes and whole skin [25]. Loss of GSH-Px 4 in the epidermis caused epidermal hyperplasia, dermal inflammatory infiltrate, dysmorphic hair follicles, and alopecia in perinatal mice [25].…”
Section: Discussionmentioning
confidence: 99%
“…Keratinocyte-specific knockout mice lacking the glutathione peroxidase 4 (GSHPx 4), an isoenzyme of GSH-Px, increased lipid peroxidation in cultured keratinocytes and whole skin [25]. Loss of GSH-Px 4 in the epidermis caused epidermal hyperplasia, dermal inflammatory infiltrate, dysmorphic hair follicles, and alopecia in perinatal mice [25]. The compound 6-CySeCD, a GSH-Px mimic, could relieve the damage induced by UV B irradiation in HaCaT cells [26].…”
Section: Discussionmentioning
confidence: 99%
“…Failure or difficulties with fibroblast growth have been previously reported both for SSMD patients and mice with ablated GPX4 4 12. Given the lack of a patient fibroblast cell line, the impact of both variants (c.587+5G>A and c.588-8_588-4del) on GPX4 splicing was assessed utilising a mini-gene system.…”
mentioning
confidence: 99%